The Use of Aerobic Gymnastics as the Means of Realizing the Objectives of School Physical Education Specific to High School Education - Piscoi, Georgeta Lucia; Dulceanu, Corina Ramona (Arena-Journal of Physical Activities, 2020)
Introduction. Aerobic gymnastics has a great influence on the locomotor system because the exercises used play an important role in shaping the shape and structure of our body, especially on the component parts of the locomotor system: bones, joints, muscles, ligaments and tendons. Methods. The use of the means and methods of aerobic gymnastics in the physical education lessons of the school will lead to the achievement of some goals of physical education and sport specific to education. Results. It was assumed that conducting physical education activities within the student training system, with the dominant application of the aerobic means, will allow to increase the influence of the instructional-educational process on the training of the necessary motor skills and experience, as well as the formation of the movement need. Some of the results obtained are: Pushups: EG/Ti = 6,3±1,63 and EG/Tf = 8,8±1,13 while CG/Ti = 5,3±1,88 and CG/Tf = 6,3±1,63; Abd.flexion: EG/Ti = 12±1,41 and EG/Tf = 14±1,5 while CG/Ti = 11±2,05 and CG/Tf = 11,6±2,01; Runing resistance: EG/Ti =4,39±0,07 and EG/Tf =3,85±0,43 while CG/Ti = 4,38±0,1 and CG/Tf = 4,35±0,08. Conclusions. The hypothesis works to confirm, this allows us to affirm that it is possible for aerobic gymnastics and to contribute to the achievement of the proposed goals and to create the physical conditions for the students by increasing significant manifestation to provide their motor and psychomotor skills.